2013
DOI: 10.1001/jamaophthalmol.2013.2500
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Complications in Children Within 1 Year After Hematopoietic Stem Cell Transplantation

Abstract: It is essential to have insights into the risk of ocular involvement after hematopoietic stem cell transplantation (HSCT) in the pediatric population because young and severely ill children are unaware of their ocular problems. Objective: To study the development of ocular complications in children within 1 year after HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ocular complications reported in children treated with TBI and or chemotherapy are cataract (Locatelli et al, 1993, De Marco et al, 1996, Suh et al, 1999, Holmstrom et al, 2002, Fahnehjelm et al, 2007, Tear Fahnehjelm et al, 2016), and dry eyes (Locatelli et al, 1993, Fahnehjelm et al, 2008, Ayuso et al, 2013, Kinori et al, 2015). Retinal haemorrhages, optic disc oedema, and chorioretinal lesions have also been described in children receiving TBI (Ayuso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular complications reported in children treated with TBI and or chemotherapy are cataract (Locatelli et al, 1993, De Marco et al, 1996, Suh et al, 1999, Holmstrom et al, 2002, Fahnehjelm et al, 2007, Tear Fahnehjelm et al, 2016), and dry eyes (Locatelli et al, 1993, Fahnehjelm et al, 2008, Ayuso et al, 2013, Kinori et al, 2015). Retinal haemorrhages, optic disc oedema, and chorioretinal lesions have also been described in children receiving TBI (Ayuso et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Retinal haemorrhages, optic disc oedema, and chorioretinal lesions have also been described in children receiving TBI (Ayuso et al, 2013). Abnormalities described in the posterior visual pathways or visual cortex are more rarely reported (Gurney et al, 2006, Gong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In children, prevalence estimates of dry eye syndrome consistent with chronic oGVHD vary widely (4%-62%). [9][10][11][12][13][14] Recently, a large prospective study using the NIH consensus criteria found that 29.4% of children had chronic oGVHD. 15 Communication barriers and lack of systematic screening in children probably lead to the underestimation of the prevalence of chronic oGVHD.…”
mentioning
confidence: 99%